Gene expression signatures in the peripheral blood after radiosurgery of human cerebral arteriovenous malformations - Zabel-du Bois, Angelika; Wagner-Ecker, Mechthild; Milker-Zabel, Stefanie; Schwager, Christian; Wirkner, Ute; Debus, Jürgen; Abdollahi, Amir; Huber, Peter E. (Strahlentherapie und Onkologie, 2010)
To unravel biological mechanisms potentially resulting in the obliteration process after radiosurgery (RS) of human cerebral arteriovenous malformations (AVMs) by investigating molecular signatures on the transcriptomic level in peripheral blood of patients.